The effect of atosiban on pregnancy outcomes in different FET cycles: a single-center matched retrospective cohort study - Yang, Yu; Luo, Rong; Qin, Shilei; Zhu, Wenkai; Yang, Minyan; Zhu, Dandan; Zhang, Ping; Wang, Jia; Ge, Hongshan (Frontiers in Endocrinology, 2025)
BackgroundThe debate over the clinical role of atosiban in assisted reproduction continues. The purpose of our study was to explore the efficacy of atosiban on pregnancy outcomes of patients undergoing frozen embryo transfer.MethodsA total of 1615 frozen embryo transfer cycles between 1 January 2019 and 31 December 2022 were included in this retrospective cohort study. Patients were divided into two groups based on the administration of atosiban before frozen-thawed embryo transfer (FET): the atosiban group (n=339) and the control group (n=1276). The primary outcome was live birth, while the secondary outcomes were biochemical pregnancy, clinical pregnancy, abortion, and ectopic pregnancy.ResultsAfter propensity score matching (PSM), both univariable and multivariable analyses showed atosiban was not linked to an increased likelihood of biochemical pregnancy or clinical pregnancy, nor a reduced risk of abortion or ectopic pregnancy (p>0.05). When controlling for confounding factors, maternal age (OR, 0.95; 95% CI, 0.91-0.98; p=0.004), history of failed ETs (1: OR, 0.72; 95% CI, 0.53-0.99; p=0.040; ≥2: OR, 0.65; 95% CI, 0.46-0.92; p=0.015), embryo stage (OR, 2.45; 95% CI, 1.85-3.25; p=0.000) and endometrial thickness (OR, 1.12; 95% CI, 1.01-1.24; p=0.025) were found to be associated with the likelihood of live birth. No beneficial effect of atosiban was observed in any of the subgroups based on maternal age, number of previous embryo transfers (ETs), endometrial thickness, or embryo stage in the subgroup analysis of the primary outcome.ConclusionThese results suggested that adding atosiban in the standard FET cycles might not improve the live birth rate. To confirm this conclusion, more thorough, prospective randomized controlled studies of sizable sample sizes with good design are required.